Mapping melodic contours on taiji diagram: taijiquan physical and philosophical perspectives in action - Loo, Fung Ying; Loo, Fung Chiat (Asian Economic and Social Society, 2013)
Some authors present in their work general association between classic Chinese philosophies such as the theory of yin and yang, Taiji and Dao and their relevance in music. This study takes this step further in selecting one of the Chinese internal martial arts, taijiquan, a physical exercise that reflects the teaching of yin and yang as a foundation to explore its possible application to piano playing. This article highlights a new mind-body concept in phrasing and melodic contour analysis in piano playing by looking at the philosophy and movement of taijiquan. More precisely, the concept of yin and yang, and how that principle works in the enactment of melodic contour, will be discussed. Methods include employing a taiji diagram in delivering an analysis of melodic contour. The question of relating the diagram as a mind-map to actual audio-physical perspectives in piano playing will be considered.